Cover Image, Volume 60, Issue 2. Issue 2 (18th January 2021) - Chaudhary, Ritu; Slebos, Robbert J. C.; Song, Feifei; McCleary‐Sharpe, Keegan P.; Masannat, Jude; Tan, Aik Choon; Wang, Xuefeng; Amaladas, Nelusha; Wu, Wenjuan; Hall, Gerald E.; Conejo‐Garcia, Jose R.; Hernanez‐Prera, Juan C.; et al.
Abstract : The cover image is based on the Research Article Effects of checkpoint kinase 1 inhibition by prexasertib on the tumor immune microenvironment of head and neck squamous cell carcinoma by Ritu Chaudhary et al., https://doi.org/10.1002/mc.23275 .